2022
DOI: 10.1186/s12929-022-00791-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic stress disrupts HGF/Met signaling in human trophoblasts: implications for the pathogenesis of preeclampsia

Abstract: Background Preeclampsia (PE), a placenta-associated pregnancy complication, is the leading cause of maternal and perinatal morbidity and mortality. Met/Erk signaling is inhibited in the placentas of patients with early-onset preeclampsia (E-PE), but the underlying mechanisms remain elusive. In this study, the expression modes of Met and endocytic vesicles in normal and preeclamptic placentas were compared. Biotinylation internalization/recycling assays were used to measure the endocytosis of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Many studies mentioned that dysfunction of the placenta in PE induced prolonged hypoxic stress. 60 61 Our results showed that oxidation-reduction process related protein TRX tend to up-regulated in model of early pregnancy of PE. Previous studies have reported that TRX is rich in the human placenta, suggesting its protective role in trophoblasts.…”
Section: Discussionmentioning
confidence: 59%
“…Many studies mentioned that dysfunction of the placenta in PE induced prolonged hypoxic stress. 60 61 Our results showed that oxidation-reduction process related protein TRX tend to up-regulated in model of early pregnancy of PE. Previous studies have reported that TRX is rich in the human placenta, suggesting its protective role in trophoblasts.…”
Section: Discussionmentioning
confidence: 59%
“…observed that upon binding to its receptor Met, HGF can activate the downstream Erk pathway, facilitating trophoblast invasion and maintaining a healthy pregnancy. While hypoxia can disrupt the regulation of the HGF/Met signaling pathway, and promoting the occurrence of PE ( 30 ). Chaudhary et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a typical microenvironmental feature of most autoimmune diseases, affecting a variety of physiological processes ( Deng et al, 2022 ; Li et al, 2022b ; Lohrasbi et al, 2022 ). One study has shown that sustained hypoxia stress can repress the CBL expression and disrupt ubiquitin degradation, leading to impaired regulation of human trophoblasts, which is the main mechanism of preeclampsia ( Li et al, 2022a ). However, it has also been shown that hypoxia induces an increase in CBL expression in H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%